ANALISIS RETURN DAN RESIKO TERHADAP KELAYAKAN INVESTASI SAHAM LQ 45 SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA TAHUN 2011-2016 - Ardiansyah Amri (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2018)
Stock giving probability of high level of return, but also giving probability of high level of risk.The alternative on stock choice and portofolio determinant can be done using many analysis tools, oneof it`s is Single Index Model. In the mining, chemical, construction and finance industries stock, only SBIinterest rate that assumed having impact on the stocks return. The purpose of this study is to measurethe size of stocks return, risk and investment expediency of LQ45 Mining Sector Stock in IndonesianStock Exchange 2011 - 2016. This study conducted using single index method. The data that used inthis study is using secondary data that acquired from active Mining Sector Stock in Indonesian StockExchange 2011 - 2016. The finding of this study shows that the proportion for the mining stock is PTBAstock 19,07%, PTGAS stock 15,21%, ITMG stock 28,65%, ANTM stock 23,34% and ADRO stock13,37%. The conclusion of this study is the 5 Mining Company Stock not qualified to be included asoptimal portofolio because of the overall ERB score that acquired from the analyisis I smaller than the Ciscore. The implication of this study is the investor suggested not to invest in the mining sector for awhile because nowadays the ming sector in Indonesia having a decreasing trend.